AN OVERVIEW ON THE TEACHING PRACTICE EXPERIENCES OF SCIENCE TEACHER CANDIDATES - Sibel DEMİR (Fırat University, 2019)
Teaching practice is one of the most important applied courses for faculties of education that train teachers. In their teaching practice experiences, teacher candidates take the first step to their professions as a result of not only their observations, but also their practices. With the aim of being able to analyze the teaching practice experiences of science teacher candidates, a rubric with which they could evaluate themselves was presented to them, and it was ensured that they would be assessed with the same rubric. Furthermore, it was expected from them to respond to this open ended question: “What would you do if you were the teacher of this class?” The aim of this study is to determine the teaching practice experiences of the science teacher candidates. The data obtained from the study were tried to be interpreted with the help of percentage comparison and content analysis. In this regard, as a result of the examining of it, it was determined that teacher candidates generally found themselves adequate, and gave various responses to the open ended questions. In conclusion, it is believed that the teaching practice experience that is an applied course in the faculties of education must be equipped with rich teaching processes as far as it can, and therefore, teacher candidates can take righter steps towards their real professional lives.